Development of Ecological Intelligence of Elementary School Students using Problem Based Instruction - Wirachman, Rony; Sapriya, Sapriya; Fauzi, Ghani Muhammad (International Conference on Elementary Education, 2020)
Life on earth is very diverse as humans, animals, plants components that exist in both land, water and air. Everything on this earth is interconnected. Humans will not be able to live without water. Likewise, if there is no land to function as a place to gather water, water will not be created on this earth. Life on earth should be safe and prosperous so that the creation of ecologically intelligent human life, attention to the place where people live socially and preserve nature. But in reality there are still humans who do not have ecological intelligence such as not yet preserving nature so that in the river there is still a lot of plastic garbage piled up, water, polluted air are all caused by human behavior itself. Elementary school students as a foundation to save the earth from various threats, therefore primary school learning must be effective which results in the creation of students who have ecological intelligence. but in reality there are still students who make rubbish randomly, use excessive plastic, preferring to buy bottled drinks rather than carrying them from home. With this problem learning must be able to have an efficient strategy. Problem Based Instruction learning related to the environment is considered to be able to change people who have ecological intelligence so that they are aware of the threat of the earth